The Role of Impulsive Buying Style and Social Media Influencers in Shaping Generation Z Consumers' Cosmetic Purchase Decisions - Samosir, Hendrik E.S.; Damanik, Hanna Meilani; Purba, Martin Luter (Law and Economics, 2025)
This study analyzes the influence of impulsive buying behavior and the role of social media influencers in shaping the consumer behavior of Generation Z within the Indonesian cosmetics industry. The objective of this research is to examine how impulsive behavior and the presence of social media influencers can shape the consumption behavior of cosmetic products. Based on the analysis of market data and consumer behavior, this study found that 49% of FMCG sales on major e-commerce platforms (Shopee, Tokopedia, Blibli) come from beauty products, with an industry growth projection of 4.59% per year until 2028. The research applies logistic regression to assess the likelihood of purchasing decisions. Social media influencers have been proven to be a key factor in increasing product awareness and triggering impulsive purchases through digital promotions and recommendations. The study reveals that Generation Z, as digital natives, are highly responsive to marketing strategies that leverage engaging content and collaborations with influencers. Data shows significant growth in Indonesia’s cosmetics industry, reaching US$8.09 billion in 2023, driven by self-care trends and increased social media usage. These findings provide strategic implications for cosmetic brands in designing effective digital campaigns to reach young consumers. The study concludes that impulsive buying styles and the presence of social media influencers enhance the probability of consumers purchasing products.